PENERIMAAN MEMBACA DAN MENULIS DI TAMAN KANAK-KANAK - Fauziah Fauziah (Universitas Dharmawangsa, 2020)
Kindergarten is a place to learn to play, so learning is through games. Where the child's world plays, by playing children will be happy, cheerful, and happy. But all that is no longer, the kindergarten was changed to a school whose lessons were like elementary school. Parents require teachers to teach reading and writing when the task of TK is to introduce a variety of knowledge, attitudes, and skills in preparation for elementary school.